Saving-capm: uma proposta de solução para o equity premium puzzle do consumption-capm - Cia, Josilmar Cordenonssi (2006)
In 1985 Mehra and Prescott raised a question that has not been answered satisfactorily: the equity premium of American shares is much higher than it could be explained by the 'neoclassical paradigm of financial economics' represented by CCAPM models. And, since then, this non-solved issue is known as the Equity Premium Puzzle (EPP). This puzzle has stimulated the production of a series of articles, theses and dissertations that tried to adjust the intertemporal expected utility models to the financial markets' data. In this context, this doctoral dissertation aims to (a) revise the historical evolution of model theory of maximization of intertemporal expected utility, (b) analyze the key assumptions and concepts of these models, (c) propose a new model that can solve the EPP, (d) apply the proposed model to the historical data between 1929 and 2004, and (e) validate the logic of this model through the MehraPrescott and Hansen-Jagannathan methodologies. This doctoral dissertation criticizes that the studies so far formulated have tried to explain the dynamics of highly sophisticated financial markets through a model of non-monetary exchange economy. Hence, its contribution consists of the changing of this assumption of a exchange economy considering that the available income of the private sector is not fully consumed, but rather also saved. Taking into account that people can obtain satisfaction (utility) with the present consumption as well as with the present savings (that will be the future consumption), it will be deduced that the marginal utility of consuming is replaced by the marginal utility of saving within the basic C-CAPM model. To reinforce this idea that the model of this doctoral dissertation uses data of savings rather than consumption, throughout the study it will be called Saving-CAPM or S-CAPM. This new model has proved to be capable of solving the EPP when submitted to the Mehra-Prescott and HansenJagannathan approaches.